2021
DOI: 10.3390/microorganisms9030580
|View full text |Cite
|
Sign up to set email alerts
|

Plant Volatiles of Lettuce and Chicory Cultivated in Aquaponics Are Associated to Their Microbial Community

Abstract: In this work, an aquaponic cultivation system for Lactuca sativa (L.) and Chicorium intybus (L.) was compared to a hydroponic one, focusing on the main microbial populations related to food safety and their volatile compounds (VOCs), concluding with Spearman correlations among the microbes and VOCs. Different sections of both systems were sampled at the end of the commercial development of the plants. Plants cultivated in aquaponics were in general more contaminated than those from hydroponics, while for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It should also be noted that the few studies that measured this metabolite in body fluids estimated low recovery in stool [40,41], which could lead us to speculate about impaired intestinal absorption in responders. Similarly, 1-hexanol 2-ethyl is a primary alcohol that occurs naturally in plants, though it is also contributed by micro-organisms [44,45]. Regarding anethole, although we were unable to distinguish its isoforms, it is worth noting that trans-anethole (from Foeniculum vulgare extracts) inhibited UV-induced melanogenesis in melanoma cells [46], thus suggesting an overall protective role.…”
Section: Discussionmentioning
confidence: 91%
“…It should also be noted that the few studies that measured this metabolite in body fluids estimated low recovery in stool [40,41], which could lead us to speculate about impaired intestinal absorption in responders. Similarly, 1-hexanol 2-ethyl is a primary alcohol that occurs naturally in plants, though it is also contributed by micro-organisms [44,45]. Regarding anethole, although we were unable to distinguish its isoforms, it is worth noting that trans-anethole (from Foeniculum vulgare extracts) inhibited UV-induced melanogenesis in melanoma cells [46], thus suggesting an overall protective role.…”
Section: Discussionmentioning
confidence: 91%
“…As shown in the present work, the microbiome altered between hybrid cultivars SR3 and SR4 and their parent cultivar JN177 was a regulator of metabolism of terpenoids and polyketides. Previous studies have indicated that volatiles organic compounds (VOCs) play significant roles in the exchange between plants and microbial communities (Li et al., 2019; Nissen et al., 2021; Piechulla et al., 2017; Raza et al., 2020;). The above results also suggested that the distant somatic hybridization can also affect the microbial communities via the shift of different metabolic pathways in the plant.…”
Section: Discussionmentioning
confidence: 99%
“…This is in comparison to more conventional production methods using soil, considering all the controllable factors in hydroponic systems that have been shown to influence the accumulation of bioactive substances [7,8], the harvest timeframe [9][10][11], and the quality of the finished product [12][13][14]. Furthermore, the lack of a soil's microbiome in hydroponic systems is also important to consider, as unsuccessful parameterization leaves the plants vulnerable to harmful spoilage by microorganisms [15][16][17].…”
Section: Introductionmentioning
confidence: 99%